2017
DOI: 10.1111/camh.12247
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mental health problems in adolescents living with HIV in Namibia

Abstract: Background Little research in sub‐Saharan Africa has looked at factors that predict mental health problems in adolescents living with HIV (ALHIV). This study examines the psychological impact of HIV in adolescents in Namibia, including risk and protective factors associated with mental health. Methods Ninety‐nine fully disclosed ALHIV between the ages of 12 and 18 were interviewed at a State Hospital in Windhoek. A structured questionnaire assessed mental health, using the SDQ (Goodman, 1997), sociodemographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 37 publications
5
23
0
Order By: Relevance
“…Principles for addressing children's mental health needs are emerging across a range of policy domains including child protection, welfare, physical health and education. These principles and practices are influenced by the emergence of findings from epidemiological research; studies about the impact of trauma on groups such as children living in orphanages, child refugees and children who have been affected by HIV; and the development and evaluation of mental health interventions for children (Gentz, Calonge, Martínez, Rosario, & Ruiz‐Casares, ; Hamdan‐Mansour, Abdel Razeq, AbdulHaq, Arabiat, & Khalil, ). A number of other factors have aided this process, and in particular, the development, testing and availability of a range of methods and instruments; their cross‐cultural validation; and the formation of international collaborative research groups.…”
mentioning
confidence: 99%
“…Principles for addressing children's mental health needs are emerging across a range of policy domains including child protection, welfare, physical health and education. These principles and practices are influenced by the emergence of findings from epidemiological research; studies about the impact of trauma on groups such as children living in orphanages, child refugees and children who have been affected by HIV; and the development and evaluation of mental health interventions for children (Gentz, Calonge, Martínez, Rosario, & Ruiz‐Casares, ; Hamdan‐Mansour, Abdel Razeq, AbdulHaq, Arabiat, & Khalil, ). A number of other factors have aided this process, and in particular, the development, testing and availability of a range of methods and instruments; their cross‐cultural validation; and the formation of international collaborative research groups.…”
mentioning
confidence: 99%
“…Among these studies, the largest effect of stigma was documented in Zambia, which found that the odds of having higher depressive symptom scores was almost three times higher for YPLHIV who experienced stigma than in those who did not (aOR = 2.99; 95% CI [1.07-8.41], p = 0.01) [94]. Having someone to talk to or feeling satisfied with health services or the social support received promoted positive mental health functioning in four studies (Namibia (n = 1) [92], Uganda (n = 2) [95,96], Zambia (n = 1) [94]. In an Ethiopian study, Abebe, Shumet [98] reported that those with low social support were 2.74 times more likely to develop depressive symptoms than those with strong social support (95% CI [1.42-5.27], p = < 0.01).…”
Section: Demographicsmentioning
confidence: 98%
“…Being female was strongly correlated with poor mental health functioning in four studies (note, the outcome definition was different in each of the four studies) [92,93,96,99]. The largest gender effect was observed in Malawi, with females almost eight times as likely compared to males to exhibit higher depression-related symptoms scores (β = 2.13, 95% CI [0.82-3.43], p = 0.002) [93].…”
Section: Demographicsmentioning
confidence: 99%
See 2 more Smart Citations